2018
DOI: 10.21315/jcdc2018.23.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Enforcement on Public Procurement Guidelines' Compliance Barriers and Cost Performance of Construction Projects in Nigerian Federal Universities: A Process Macro Approach

Abstract: (2018). Mediating effects of enforcement on public procurement guidelines' compliance barriers and cost performance of construction projects in Nigerian federal universities: A process macro approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Corrupt consultants request different gratifications from contractors that end up reducing contractors' profit margin or leading to a loss. Results from this study amplify the call for enforcement of public procurement guidelines in public projects (Zadawa et al, 2018). A significant relationship exists between the design and management risk centre and PRIC (b = 0.306).…”
Section: Road Projects In Developing Countriessupporting
confidence: 66%
“…Corrupt consultants request different gratifications from contractors that end up reducing contractors' profit margin or leading to a loss. Results from this study amplify the call for enforcement of public procurement guidelines in public projects (Zadawa et al, 2018). A significant relationship exists between the design and management risk centre and PRIC (b = 0.306).…”
Section: Road Projects In Developing Countriessupporting
confidence: 66%
“…Questionnaires were validated following a pilot study involving construction managers and procurement officers in New South Wales, Australia. The validation involved rewording to avoid ambiguous statements (Zadawa et al, 2018). Smart-PLS3 software with PLS algorithms option was performed to obtain measurement indicators.…”
Section: Reliability and Validitymentioning
confidence: 99%
“…A lack of compliance in public procurement affects transparency and accountability and leads to failing public construction projects, for example, in Nigeria (Zadawa et al, 2018), Gaza strip (Tayeh et al, 2018) and the UK (Gledson et al, 2018). In Australia, when comparing the public with the private sector, Kling (2008) suggested that the private sector leads to efficient and less costly procurement practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges impact project performance, often with cascading effects on other projects. Researchers have reported examples of performance problems due to issues with cost and time in projects in different countries, for example, in Australia [8], Nigeria [9], Gaza Strip [4], UK [10], Ghana [11], and Kenya [12].…”
Section: Construction Projects and Their Importancementioning
confidence: 99%